2010
DOI: 10.1071/mf09151
|View full text |Cite
|
Sign up to set email alerts
|

Towards better management of Australia's shark fishery: genetic analyses reveal unexpected ratios of cryptic blacktip species Carcharhinus tilstoni and C. limbatus

Abstract: The common blacktip shark (Carcharhinus limbatus) and the Australian blacktip shark (C. tilstoni) are morphologically similar species that co-occur in subtropical and tropical Australia. In striking contrast to what has been previously reported, we demonstrate that the common blacktip shark is not rare in northern Australia but occurs in approximately equal frequencies with the Australian blacktip shark. Management of shark resources in northern Australia needs to take account of this new information. Species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 25 publications
7
68
0
Order By: Relevance
“…The observation that there are greater differences in the COI barcode sequence among populations of the same nominal species (C. amblyrhynchoides) than there are between individuals of different species (C. leiodon and C. amblyrhynchoides) could give pause to those who would base species description on sequence data without a thorough sampling of all of the geographic variation circumscribed by a given species. Our data are consistent with the close relationship of C. amblyrhynchoides, C. limbatus and C. tilstoni suggested by Ward et al (2008) and recently confirmed by Ovenden et al (2010), who in addition to COI, used sequences from the control region and ND4 regions of the mitochondrial genome. However, the exact inferred relationships differ among studies.…”
Section: Molecular Analysessupporting
confidence: 80%
“…The observation that there are greater differences in the COI barcode sequence among populations of the same nominal species (C. amblyrhynchoides) than there are between individuals of different species (C. leiodon and C. amblyrhynchoides) could give pause to those who would base species description on sequence data without a thorough sampling of all of the geographic variation circumscribed by a given species. Our data are consistent with the close relationship of C. amblyrhynchoides, C. limbatus and C. tilstoni suggested by Ward et al (2008) and recently confirmed by Ovenden et al (2010), who in addition to COI, used sequences from the control region and ND4 regions of the mitochondrial genome. However, the exact inferred relationships differ among studies.…”
Section: Molecular Analysessupporting
confidence: 80%
“…PCR was then used to amplify the mitochondrial ND4 gene from all DNA extractions. This gene was selected for analysis following Dudgeon et al (2009) and Ovenden et al (2010), who demonstrated the ND4 gene to be the most polymorphic among a range of mtDNA markers (including the control region) in species related to those under study here. PCR reactions were carried out in 50 µl volumes containing 1 µl of DNA template, 1× GoTaq Colourless reaction buffer (consisting of 1.5 mM MgCl 2 and 200 µM deoxynucleoside triphosphates [dNTPs]) (Promega), 0.5 µl of RNase (1 mg ml −1 ), and 0.5 µM of each of the primers ND4 (5' CAC CTA TGA CTA CCA AAA GCT CAT GTA GAA GC) (Arèvalo et al 1994) and H12293-LEU (5' TTG CAC CAA GAG TTT TTG GTT CCT AAG ACC) (Inoue et al 2001).…”
Section: Dna Extraction Amplification and Sequencingmentioning
confidence: 99%
“…Given that the degree of spatial and temporal overlap and hybridisation of C. tilstoni and C. limbatus remains unclear (Ovenden et al 2010, Morgan et al 2011, Tillett et al 2012, and that these 2 species demonstrate differential susceptibility to harvest, managers must attempt to estimate their relative contributions in catches. Our models indicate that the more C. limbatus is represented in catches, the lower the harvest rate the combined population can tolerate.…”
Section: Discussionmentioning
confidence: 99%